THE MEASUREMENT METHODOLOGY IMPROVEMENT OF THE HORIZONTAL IRREGULARITIES IN PLAN - Patlasov, O. M.; Tokariev, S. O. (Science and Transport Progress, 2015)
Purpose. Across the track superstructure (TSS) there are structures where standard approach to the decision on the future of their operation is not entirely correct or acceptable. In particular, it concerns the track sections which are sufficiently quickly change their geometric parameters: the radius of curvature, angle of rotation, and the like. As an example, such portions of TSS may include crossovers where their component is within the so-called connecting part, which at a sufficiently short length, substantially changes curvature. The estimation of the position in terms of a design on the basis of the existing technique (by the difference in the adjacent arrows bending) is virtually impossible. Therefore it is proposed to complement and improve the methodology for assessing the situation of the curve in plan upon difference in the adjacent versine. Methodology. The possible options for measuring horizontal curves in the plan were analyzed. The most adequate method, which does not contradict existing on the criterion of the possibility of using established standards was determined. The ease of measurement and calculation was took into account. Findings. Qualitative and quantitative verification of the proposed and existing methods showed very good agreement of the measurement results. This gives grounds to assert that this methodology can be recommended to the workers of track facilities in the assessment of horizontal irregularities in plan not only curves, but also within the connecting part of switch congresses. Originality. The existing method of valuation of the geometric position of the curves in the plan was improved. It does not create new regulations, and all results are evaluated by existing norms. Practical value. The proposed technique makes it possible, without creating a new regulatory framework, to be attached to existing one, and expanding the boundaries of its application. This method can be used not only for ordinary curves, but for very short sections, the curvature of which changes abruptly to its opposite value.